2018
DOI: 10.1097/meg.0000000000001206
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anastomotic recurrence after primary ileocaecal resection in Crohn’s disease

Abstract: Urgent surgery and postoperative corticosteroid need represented risk factors for anastomotic recurrence. Hand-sewn anastomosis with an opening of the bowel's antimesenteric border seems to be a safe choice for ileocaecal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Anastomotic margin recurrence has been reported in 34% after primary ileocecal resection. [11] Endoscopic balloon dilatation should be the primary intervention for surgery in experienced centers in strictures and obstructions caused by CD; however, surgical treatment is still in the foreground in most centers. [12,13] The priority of evacuation of abscesses due to CD can be left to percutaneous drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic margin recurrence has been reported in 34% after primary ileocecal resection. [11] Endoscopic balloon dilatation should be the primary intervention for surgery in experienced centers in strictures and obstructions caused by CD; however, surgical treatment is still in the foreground in most centers. [12,13] The priority of evacuation of abscesses due to CD can be left to percutaneous drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding and cancer development are less common surgical indications. [3,5,[9][10][11] Obstruction due to stenosis due to chronic recurrent inflammation and fibrosis is one of the most common indications for surgery and the most common surgical procedure is ileocecal resection. This was also consistent with our series since 153 patients (79.7%) underwent ileocecal resection only.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the risk factors associated with postoperative recurrence will markedly benefit patients with CD and will permit doctors to maintain close postoperative surveillance in high-risk cases and optimize CD therapy[ 17 , 18 ]. Although there are conflicting results in the reports according to whether the perforating indication for surgery affects postoperative recurrence[ 19 , 20 ], some studies have indicated that perforating CD is a risk factor for earlier recurrence[ 21 ]. Our results showed that the perforating indication was a predictor of surgical recurrence, which confirmed the concept that the perforating indication for surgery was associated with decreased recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Gajendran concluded that, according to his data, the restoration of physiologic intestinal function with surgical reconstruction of the bowel as an intact tube could contribute to a better outcome in CD patients. In the same year, Aaltonen’s group [ 75 ] published its series regarding risk factors for anastomotic recurrence. Aaltonen’s et al proposed a technical variant HEEA, adding an opening of the small bowel’s anti-mesenteric border to ensure enough wide bowel lumen, describing this modified technique as a safe choice for ileo-colonic resection.…”
Section: Por: New Discoveries and Trendsmentioning
confidence: 99%